2019
DOI: 10.1111/gcbb.12648
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas budget of a poplar bioenergy plantation in Belgium: CO2 uptake outweighs CH4 and N2O emissions

Abstract: Biomass from short‐rotation coppice (SRC) of woody perennials is being increasingly used as a bioenergy source to replace fossil fuels, but accurate assessments of the long‐term greenhouse gas (GHG) balance of SRC are lacking. To evaluate its mitigation potential, we monitored the GHG balance of a poplar (Populus) SRC in Flanders, Belgium, over 7 years comprising three rotations (i.e., two 2 year rotations and one 3 year rotation). In the beginning—that is, during the establishment year and during each year im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
(92 reference statements)
2
10
0
Order By: Relevance
“…Even though the important role of SRC plantations in bioenergy productions and carbon sequestration is well recognized by the scientific community [10,11], data on SRC productivity (e.g., Gross Primary Productivity (GPP)) and phenology are scarce and limited to small experimental areas.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the important role of SRC plantations in bioenergy productions and carbon sequestration is well recognized by the scientific community [10,11], data on SRC productivity (e.g., Gross Primary Productivity (GPP)) and phenology are scarce and limited to small experimental areas.…”
Section: Introductionmentioning
confidence: 99%
“…To conclude, this study showed that 10‐year rotation produced significantly more sustainable biomass in comparison to two, consecutive 5‐year rotation cycles. Other advantages of longer rotations arise from less impact on environment (Griffiths et al, 2019), a better GHG budget (creation of a GHG sink; Horemans et al, 2019) and positive influences on biodiversity (Griffiths et al, 2019), which together make them more similar to forest systems. Such rotations use the biological growth abilities of the trees more naturally.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cellulosic ethanol derived from plants such as hybrid poplar can reduce net GHG emissions to nearly zero (Solomon et al, 2007 ). Researchers found that in a poplar short-rotation coppice in Belgium, the bioenergy plantation's high CO 2 uptake outweighed non-CO 2 greenhouse gas emissions (Horemans et al, 2019 ). The chemical properties and ubiquity of the secondary cell wall (SCW) have led to the SCW being marked as a biofuel source of interest.…”
Section: Introductionmentioning
confidence: 99%